Translation and UK Political Agendas, with special reference to W. Churchill, M. Thatcher and T. Blair - ZEDAIK, Meriem; AFKIR ,Mohamed (Faculty of Letters and Foreign Languages Department of English, 2025)
This dissertation seeks to investigate the role of translation to serve political agendas in the UK. Particularly it examines the correlation between translation and political discourse through the study of Britain’s Prime Ministers Winston Churchill, Margaret Thatcher and Tony Blair. This study explores how translation functions not only as a linguistic tool but also as a political instrument used to manipulate meaning and reshape thoughts, thus affecting opinions and even draw biased political ideologies. This research also highlights the potential of translation through which the reception of the political message is received across different cultural, linguistic and political contexts. Through implementing a qualitative analysis of the case studies of Churchill, Thatcher, and Blair’s speeches and analysis of rhetorical, ideological, and cultural translation shifts, this dissertation argues that translation is used by political leaders to project authority, maintain power and spread domination by shaping a national identity. It suggests that translation can be a powerful, strong determining tool of political persuasion rather than being a neutral means of transferring language. Translation often contributes to the legitimization of political authority as it plays a role beyond the linguistic scope.